Cofactor‐independent human antiphospholipid antibodies induce venous thrombosis in mice. (16th March 2016) - Manukyan, D.; Müller‐Calleja, N.; Jäckel, S.; Luchmann, K.; Mönnikes, R.; Kiouptsi, K.; Reinhardt, C.; Jurk, K.; Walter, U.; Lackner, K. J.
Abstract : Essentials Cofactor‐independent antiphospholipid antibodies (CI‐aPL) are generally considered non‐pathogenic. We analyzed the effects of human monoclonal CI‐aPL in a mouse model of venous thrombosis. As shown in vitro, CI‐aPL induce a procoagulant state in vivo by activation of endosomal NADPH‐oxidase. Contrary to common belief, CI‐aPL induce venous thrombosis in vivo . Summary: Background: There is general consensus that the antiphospholipid syndrome (APS) is caused by antiphospholipid antibodies (aPL) with antibodies against β2‐glycoprotein‐I being the most relevant. aPL that bind phospholipids in the absence of protein cofactors are generally considered pathogenetically irrelevant. We showed that cofactor‐independent human monoclonal aPL isolated from APS patients induce proinflammatory and procoagulant cellular responses by activating endosomal NADPH‐oxidase 2 (NOX2). Similar aPL were detected in all IgG fractions from APS patients analyzed. Objectives: We aimed to clarify if cofactor‐independent aPL can be thrombogenic in vivo and, if so, whether these effects are mediated via activation of NOX2. Methods: Two cofactor‐independent human monoclonal aPL, HL5B and RR7F, were tested in a mouse model of venous thrombosis. Genetically modified mice and in vitro assays were used to delineate the mechanisms underlying thrombus induction. Results: HL5B and RR7F dramatically accelerate thrombus formation in this mouse model. Thrombus formation depends on tissue factor activation. It cannot be induced in NOX2‐deficient mice. Bone marrow chimeras of C57BL/6J mice reconstituted with NOX2‐deficient bone marrow showed that leukocyte activation plays a major role in thrombus formation. Neither TLR4 signaling nor platelet activation by our aPL is required for venous thrombus formation. Conclusions: Cofactor‐independent aPL can induce thrombosis in vivo . This effect is mainly mediated by leukocyte activation, which depends on the previously described signal transduction via endosomal NOX2. Because most APS patients have been shown to harbor aPL with similar activity, our data are of general relevance for the APS.